2022
DOI: 10.3390/microorganisms10030633
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin Does Not Protect against SARS-CoV-2 Infection in the Syrian Hamster Model

Abstract: Ivermectin, an FDA-approved antiparasitic drug, has been reported to have in vitro activity against SARS-CoV-2. Increased off-label use of ivermectin for COVID-19 has been reported. We here assessed the effect of ivermectin in Syrian hamsters infected with the SARS-CoV-2 Beta (B.1.351) variant. Infected animals received a clinically relevant dose of ivermectin (0.4 mg/kg subcutaneously dosed) once daily for four consecutive days after which the effect was quantified. Ivermectin monotherapy did not reduce lung … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…67 A study (400 µg/kg of IVM per day over four days) showed an overall lack of efficacy in Syrian hamnsters. 68 Another study in hamsters showed no decrease in viral load but reported attenuation of clinical and immunological outcomes by invoking a potential immunomodulatory mechanism distinct from the original hypothesized importin target. 69 Our work suggests that IVM, and other compounds with similar modes of action, could be flagged earlier in the translation process, perhaps prior to transitioning from culture monolayers to more physiological models (e.g., which incorporate apical air and basolateral medium compartments) by testing for their (subtle) membrane-perturbing effects.…”
Section: Discussionmentioning
confidence: 99%
“…67 A study (400 µg/kg of IVM per day over four days) showed an overall lack of efficacy in Syrian hamnsters. 68 Another study in hamsters showed no decrease in viral load but reported attenuation of clinical and immunological outcomes by invoking a potential immunomodulatory mechanism distinct from the original hypothesized importin target. 69 Our work suggests that IVM, and other compounds with similar modes of action, could be flagged earlier in the translation process, perhaps prior to transitioning from culture monolayers to more physiological models (e.g., which incorporate apical air and basolateral medium compartments) by testing for their (subtle) membrane-perturbing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the efficacy of molnupiravir in Syrian hamsters inoculated with SARS-CoV-2 were carried out with doses ranging from 50 to 500 mg/kg twice daily [41][42][43][44][45][46][47][48][49][50]. Specifically, a dose-response study suggested that a 150 mg/kg dose of molnupiravir twice daily was suboptimal, and that a dose of at least 200 mg/kg twice daily was necessary to reduce pulmonary viral titers to levels near the detection limit [43].…”
Section: Dose Levels Of Molnupiravirmentioning
confidence: 99%
“…Several of the animal studies aimed to assess the effect of combining molnupiravir with another agent including an antiviral. These studies used a suboptimal dose of molnupiravir to compare its effect in monotherapy with that observed in combination therapies, thereby facilitating the detection of potential synergistic effects [10,39,41,43,44,46]. For example, a suboptimal molnupiravir dose of 150 mg/kg twice daily was used in Syrian hamsters [43,44,46].…”
Section: Dose Levels Of Molnupiravirmentioning
confidence: 99%
See 1 more Smart Citation